2008 International Conference on Field Programmable Logic and Applications 2008
DOI: 10.1109/fpl.2008.4630015
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of embedded reconfigurable video-processing architectures

Abstract: Using Field Programmable Gate Arrays (FPGAs) as accelerators for image or video processing operations and algorithms has gained increasing attention over the last few years. One reason for that is FPGAs are able to exploit both temporal and spatial parallelism. In this paper two platforms for FPGA-based real-time image and video processing are presented and compared against each other. With both of these platforms it is possible to update the physical resources during run-time by exploiting the dynamic partial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Recent work in partial reconfiguration of FPGAs provides insight into the stateof-the-art. Claus et al [10] give a comparison of embedded reconfigurable videoprocessing architectures. They propose a hybrid of two hardware platforms: one providing easy reconfiguration of modules and the other providing easy implementation with higher clock frequency, to achieve an optimal FPGA-based dynamically and partially reconfigurable platform for real-time video and image processing.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Recent work in partial reconfiguration of FPGAs provides insight into the stateof-the-art. Claus et al [10] give a comparison of embedded reconfigurable videoprocessing architectures. They propose a hybrid of two hardware platforms: one providing easy reconfiguration of modules and the other providing easy implementation with higher clock frequency, to achieve an optimal FPGA-based dynamically and partially reconfigurable platform for real-time video and image processing.…”
Section: Background and Related Workmentioning
confidence: 99%
“…Recent works in partial reconfiguration of FPGAs implement DWT in a reconfigurable fashion. Claus et al (2008) gives a comparison of embedded reconfigurable video-processing architectures. They propose a hybrid of two hardware platforms: one providing easy reconfiguration of modules and the other providing easy implementation with higher clock frequency, to achieve an optimal FPGA-based dynamically and partially reconfigurable platform for real-time video and image processing.…”
Section: Reconfigurable Hardware Implementationmentioning
confidence: 99%
“…DPR has been used for streaming vision processing [3], [4] at a coarse time-scale, where the time between reconfigurations is within seconds to minutes range, to repurpose the FPGA for different functionalities. In [11], the authors identified the issues of asynchronous module execution and frame skipping when applying DPR for repurposing in a vision streaming context. Streaming Vision Pipeline.…”
Section: Introductionmentioning
confidence: 99%